Effect of physical environment on survival of Helicobacter pylori. - West, A. P. (1992)
AIMS: To determine the effects of physical conditions on survival of Helicobacter pylori in aquatic environments. Survival for prolonged time intervals would implicate environmental water as a possible source of infection. METHODS: The effect of ionic strength, pH, urea, protein and composition of incubation atmosphere on the survival of H pylori NCTC 11637 and two clinical isolates (CI 82 and 92) was investigated. RESULTS: H pylori strains survived for longer periods in physiological (0.15M) saline than in 0.05M or 0.6M saline solution. Optimal pH range for survival was between pH 5.8 and 6.9. Addition of urea (final concentration 100 microM/l-1 and 5 mM/l-1) to neutral unbuffered 0.15M saline resulted in a reduction in survival; addition of bovine serum albumin (1%) or gelatin (1%) resulted in variable survival times compared with saline alone. Incubation in a microaerobic gas mixture prolonged survival compared with incubation in air. CONCLUSION: H pylori survival in water over a prolonged period is possible for a range of physical variables. The results indicate that H pylori could survive in environmental water which may thus act as a potential reservoir of infection.